Antioxidant and Antimicrobial Activity of Alpinia officinarum - Srividya, A. R. (Medknow Publications, 2010)
Alpinia officinarum is a rhizome belonging to the family zingeberaeceae. Hydro alcoholic extract by hot and cold maceration and methanol extract by percolation process Qualitative phytochemical analysis of extract of Alpinia officinarum rhizome showed a majority of the compound including tannins, alkaloids, flavonoids and saponins. Hydroalcoholic extract prepared by hot maceration process was found to contain more phenol and flavonol and it was measured as 50.1 mg/g and 54.02 mg/g, respectively. All the three extracts showed moderate to potent antimicrobial activity against the Bacillus cereus, Staphylococcus aureas, Pseudomonas auroginosa, Escherichia coli. None of the extracts showed antifungal activity against Aspergillus niger and Candida albicans. All the three extracts showed a concentration dependent radical scavenging activity by inhibiting diphenylpicrylhydrazyl free radical at the same time hydroalcoholic extract prepared by hot maceration process showed better reducing and total antioxidant activity.